Development of antimicrobial polyester fabric by a green in-situ synthesis of copper nanoparticles mediated from chitosan and ascorbic acid - Mehravani, Behnaz (2022)
The antimicrobial functionalization of polyester fabrics (PES) is useful to provide protection from pathogens and reducing odors. Copper nanoparticles (CuNPs) have been widely applied due to their antimicrobial properties and higher biocompatibility compared with other metal nanoparticles. However, the inherent instability of CuNPs under atmospheric conditions and the use of harmful chemicals during their synthesis limit their use. Thus, the development of efficient and safe methods for the CuNPs synthesis and their stabilization onto surfaces present high interest. In this work, PES was functionalized with CuNPs via in situ synthesis using cost-effective and safe chemicals in the presence and absence of chitosan. In sample without chitosan, the CuNPs showed a suitable stabilization onto PES due to the doubled stabilization of ascorbic acid (AA) and cetyl trimethyl ammonium bromide (CTAB). In sample with chitosan, less CuNPs were retained by the PES but also less CuNPs agglomeration was observed. Both samples presented excellent antibacterial effect against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) as well as laundering durability.